Kontribusi Pendekatan Sosiologi dalam Pengembangan Kajian Al-Qur’an dan Tafsir: Perspektif Teoretis dan Praktis - Didik Harianto; Putroe Balqis (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
Contemporary Qur’anic exegetical studies demonstrate a strong tendency toward multidisciplinary approaches, one of which is the integration of sociological perspectives. This approach is significant because the Qur’an functions not only as a normative text but also as a guide that interacts with dynamic social realities. This article aims to analyze the contribution of sociological approaches to the development of Qur’anic exegetical methodology, to explain the application of sociological theories in the analysis of Qur’anic verses, and to assess the relevance and challenges of integrating sociological perspectives into tafsir studies. Employing a qualitative approach through library research on classical and contemporary tafsir literature, works in the sociology of religion, and related studies, this article finds that sociological approaches play an important role in the contextualization of verses, the development of thematically oriented tafsir based on social issues, and responses to contemporary socio-religious problems such as social justice, gender equality, and environmental crises. Nevertheless, this approach also faces methodological and theological challenges, particularly the potential for tension with normative exegetical interpretations. The article concludes that the integration of sociology enriches Qur’anic exegesis when applied critically and grounded in the established principles of tafsir methodology.